If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2(-7 + 21) = 0 Combine like terms: -7 + 21 = 14 7x + 2(14) = 0 Multiply 2 * 14 7x + 28 = 0 Reorder the terms: 28 + 7x = 0 Solving 28 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 7x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 7x = 0 + -28 7x = 0 + -28 Combine like terms: 0 + -28 = -28 7x = -28 Divide each side by '7'. x = -4 Simplifying x = -4
| 0.3333(v+100)=500 | | 5x+0.3=5.6 | | 22d^2-31d=0 | | -2.66x-(-2.5)=-1.5 | | 3y+6=-x | | -4x-2(3x-10)=80 | | -2x+3=-2(x+3) | | -2x+5(-3x+26)=-57 | | 3x^2+4x-7=13 | | 5x+8y-3=0 | | (8n^2-n+5)(4n^2+2n+2)= | | 3x+4(-4x-27)=35 | | 3-2x=5+3x | | -5p+8=2(3p-2)-3(-8+5p) | | 7-x=-8-x | | -6=n-210 | | 5n+10n=6.35 | | T-42=3 | | 1/2(x+6)=3/2x-1 | | 14+7(x-9)=28 | | 4y+12=-3x | | -(m+6n-13)= | | 2r=1.33r+8 | | (2n^2+5n+8)(2n^2-6n-1)= | | 15+10p-8=p+9p+13 | | -19th+12=-14th-8 | | -5x-7(-2x+3)=-66 | | 3+2.7x=4.7 | | 3(2x-5)=5(x-4)1x+5 | | 3z=-7+17 | | 8k-4.7=3k+0.4 | | 28=-48 |